Synthesis of indole-based propellane derivatives via Weiss–Cook condensation, Fischer indole cyclization, and ring-closing metathesis as key steps - Kotha, Sambasivarao; Chinnam, Ajay Kumar; Tiwari, Arti (Beilstein Journal of Organic Chemistry, 2013)
A variety of highly functionalized indole-based [n.3.3]propellane derivatives is described. The synthesis of the propellane derivatives involves a Weiss–Cook condensation, a Fischer indole cyclization, and a ring-closing metathesis as key steps.
Keywords: allylation; indole derivatives; propellanes; ring-closing metathesis; Weiss–Cook condensation

Propellanes Structure and Reactions - Ginsburg, D. (Verlag Chemie, 1975)

Propellanes Structure and Reactions (Sequel I) - Ginsburg, D. (Department of Chemistry, Technion, 1981)

Propellanes Structure and Reactions (Sequel II) - Ginsburg, D. (Department of Chemistry, Technion, 1985)

(untitled) - Ginsburg, D. (Top. Curr. Chem., 1987)

(untitled) - Pihko, A. J.; Koskinen, A. M. P. (Tetrahedron, 2005)

Indoles - Sundberg, R. J. (Academic Press, 1996)

(untitled) - Gilchrist, T. L. (J. Chem. Soc., Perkin Trans. 1, 1999)

(untitled) - Gribble, G. W. (J. Chem. Soc., Perkin Trans. 1, 2000)

(untitled) - Makosza, M.; Wojciechowski, K. (Heterocycles, 2001)

(untitled) - Battistuzzi, G.; Cacchi, S.; Fabrizi, G. (Eur. J. Org. Chem., 2002)

(untitled) - Cacchi, S.; Fabrizi, G. (Chem. Rev., 2005)

(untitled) - Humphrey, G. R.; Kuethe, J. T. (Chem. Rev., 2006)

(untitled) - Brown, K. S., Jr; Budzikiewicz, H.; Djerassi, C. (Tetrahedron Lett., 1963)

(untitled) - Walser, A.; Djerassi, C. (Helv. Chim. Acta, 1965)

Indolalkaloide in Tabellen-Ergänzungswerk - Hesse, M. (Springer-Verlag, 1968)

(untitled) - Honma, Y.; Ohnuma, T.; Ban, Y. (Heterocycles, 1976)

(untitled) - Ban, Y.; Ohnuma, T.; Seki, K.; Oishi, T. (Tetrahedron Lett., 1975)

(untitled) - Yoshida, K.; Sakuma, Y.; Ban, Y. (Heterocycles, 1987)

(untitled) - Campbell, E. L.; Zuhl, A. M.; Lui, C. M.; Boger, D. L. (J. Am. Chem. Soc., 2010)

(untitled) - Mitaine, A.-C.; Mesbah, K.; Richard, B.; Petermann, C.; Arrazola, S.; Moretti, C.; Zèches-Hanrot, M.; Le Men-Olivier, L. (Planta Med., 1996)

(untitled) - Awang, K.; Sévenet, T.; Païs, M.; Hadi, H. A. (J. Nat. Prod., 1993)

(untitled) - Yap, W.-S.; Gan, C.-Y.; Low, Y.-Y.; Choo, Y.-M.; Etoh, T.; Hayashi, M.; Komiyama, K.; Kam, T.-S. (J. Nat. Prod., 2011)

(untitled) - Kam, T.-S.; Lim, K.-H.; Yoganathan, K.; Hayashi, M.; Komiyama, K. (Tetrahedron, 2004)

(untitled) - Schultz, E. E.; Pujanauski, B. G.; Sarpong, R. (Org. Lett., 2012)

(untitled) - Massiot, G.; Thépenier, P.; Jacquier, M.-J.; Le Men-Olivier, L.; Delaude, C. (Heterocycles, 1989)

(untitled) - Dounay, A. B.; Overman, L. E.; Wrobleski, A. D. (J. Am. Chem. Soc., 2005)

(untitled) - Dounay, A. B.; Humphreys, P. G.; Overman, L. E.; Wrobleski, A. D. (J. Am. Chem. Soc., 2008)

(untitled) - Shen, L.; Zhang, M.; Wu, Y.; Qin, Y. (Angew. Chem., Int. Ed., 2008)

(untitled) - Jones, S. B.; Simmons, B.; MacMillan, D. W. C. (J. Am. Chem. Soc., 2009)

(untitled) - Li, G.; Padwa, A. (Org. Lett., 2011)

(untitled) - Liu, P.; Wang, J.; Zhang, J.; Qiu, F. G. (Org. Lett., 2011)

(untitled) - Ramírez, A.; García-Rubio, S. (Curr. Med. Chem., 2003)

(untitled) - Elsebai, M. F.; Rempel, V.; Schnakenburg, G.; Kehraus, S.; Müller, C. E.; König, G. M. (ACS Med. Chem. Lett., 2011)

(untitled) - Pacher, P.; Bátkai, S.; Kunos, G. (Pharmacol. Rev., 2006)

(untitled) - Cox, E. D.; Cook, J. M. (Chem. Rev., 1995)

(untitled) - Bertz, S. H.; Cook, J. M.; Gawish, A.; Weiss, U. (Org. Synth., 1986)

Heterocyclic Scaffolds II: Reactions and Applications of Indoles - Gribble, G. W. (Springer, 2010)

(untitled) - Inman, M.; Moody, C. J. (Chem. Sci., 2013)

(untitled) - Kotha, S.; Dipak, M. K. (Chem.–Eur. J., 2006)

(untitled) - Kotha, S.; Lahari, K. (Synlett, 2007)

(untitled) - Kotha, S.; Chavan, A. S.; Dipak, M. K. (Tetrahedron, 2011)

(untitled) - Kotha, S.; Dipak, M. K. (Tetrahedron, 2012)

(untitled) - Kotha, S.; Hollinshead, S.; Grubisha, D.; Laib, F.; Bennett, D.; Cook, J. M. (J. Org. Chem., 1990)

(untitled) - Paquette, L. A.; Crouse, G. D. (J. Org. Chem., 1983)

(untitled) - Deshpande, M. N.; Jawdosiuk, M.; Kubiak, G.; Venkatachalam, M.; Weiss, U.; Cook, J. M. (J. Am. Chem. Soc., 1985)

(untitled) - Fu, X.; Cook, J. M. (J. Org. Chem., 1992)

(untitled) - Fu, X.; Cook, J. M. (Aldrichimica Acta, 1992)

(untitled) - Gupta, A. K.; Fu, X.; Snyder, J. P.; Cook, J. M. (Tetrahedron, 1991)

(untitled) - Weiss, U.; Edwards, J. M. (Tetrahedron Lett., 1968)

(untitled) - Yang, S.; Cook, J. M. (J. Org. Chem., 1976)

(untitled) - Miller, S. J.; Kim, S.-H.; Chen, Z.-R.; Grubbs, R. H. (J. Am. Chem. Soc., 1995)

(untitled) - Maier, M. E. (Angew. Chem., Int. Ed., 2000)

(untitled) - Tori, M.; Mizutani, R. (Molecules, 2010)